HUBUNGAN KEGIATAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DENGAN PENGEMBANGAN KARAKTER GOTONG ROYONG SISWA KELAS V SD NEGERI 7 ARAWA KABUPATEN SIDENRENG RAPPANG - Sudirman; Achmad Shabir; Widya Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is a type of symmetric correlational research and uses a quantitative approach which aims to determine whether or not there is a relationship between project activities to strengthen the profile of Pancasila students and the development of the mutual cooperation character of class V students at SD Negeri 7 Arawa, Sidenreng Rappang Regency. The population in this study were all students at SD Negeri 7 Arawa. The sample in this research consisted of 25 students. Data collection techniques were carried out using observation sheets and questionnaires. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis. The results of descriptive statistical analysis of P5 activities obtained an average of 51.24, while mutual cooperation character development obtained an average of 53.64 in the medium category. The results of inferential statistics show rcount > rtable (0.944 > 0.3365) at a significance level of 5%, which means there is a positive relationship. Thus H1 is accepted and H0 is rejected. This research concludes that there is a significant the correlation between project Based Learning for strengthening pancasila student profile and the development of collaborative character in grade five students at SD Negeri 7 Arawa, Sidenreng Rappang District.